2009
DOI: 10.1038/labinvest.2008.67
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of genetic alterations in Barrett's adenocarcinoma using single nucleotide polymorphism arrays

Abstract: We performed genome-wide analysis of copy-number changes and loss of heterozygosity (LOH) in Barrett's esophageal adenocarcinoma by single nucleotide polymorphism (SNP) microarrays to identify associated genomic alterations. DNA from 27 esophageal adenocarcinomas and 14 matching normal tissues was subjected to SNP microarrays. The data were analyzed using dChipSNP software. Copy-number changes occurring in at least 25% of the cases and LOH occurring in at least 19% were regarded as relevant changes. As a valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 41 publications
3
30
2
Order By: Relevance
“…(177) (195) (Continued on the following page) decade, several studies conducted using advanced genomic techniques such as array-comparative genomic hybridization (aCGH) and SNP arrays confirmed previously reported copy number alterations and identified novel genomic loci undergoing changes during process of metaplasia-dysplasia-carcinoma development (54)(55)(56)(57)(58)(59)(60). It has been shown that as the disease progresses from early to late stages, SNP abnormalities increase from approximately 2% to 30% (54,57).…”
Section: Genomic Instabilitymentioning
confidence: 77%
See 1 more Smart Citation
“…(177) (195) (Continued on the following page) decade, several studies conducted using advanced genomic techniques such as array-comparative genomic hybridization (aCGH) and SNP arrays confirmed previously reported copy number alterations and identified novel genomic loci undergoing changes during process of metaplasia-dysplasia-carcinoma development (54)(55)(56)(57)(58)(59)(60). It has been shown that as the disease progresses from early to late stages, SNP abnormalities increase from approximately 2% to 30% (54,57).…”
Section: Genomic Instabilitymentioning
confidence: 77%
“…It has been shown that as the disease progresses from early to late stages, SNP abnormalities increase from approximately 2% to 30% (54,57). The total number of SNP alterations in tissue samples is tightly correlated with previously reported DNA abnormalities such as aneuploidy, copy number alterations, and LOH highlighting the application of SNP-based genotyping to assess genomic abnormalities (54)(55)(56)(57)(58)(59)(60). Thus, SNP-based genotyping provides an alternative way to assess genomic abnormalities during EAC pathogenesis.…”
Section: Genomic Instabilitymentioning
confidence: 96%
“…Consequently it is complicated to interpret the most recent results of Ihsan et al (15), since additionally the overall data report inconsistent findings regarding esophageal cancer risk. Moreover, three recently performed genome-wide association studies, using detection of SNPs or cDNA microarray techniques, did not identify the EPHX1 gene as a susceptibility locus for ESCC or EAC (26)(27)(28).…”
Section: Exon 4 -----------------------------------------------------mentioning
confidence: 99%
“…Recently, array-based comparative genomic hybridization (aCGH) or single nucleotide polymorphism (SNP) array have detected novel candidate genes involved in development and progression of Barrett's carcinoma. Among them, SOX7 5 and SNRPN 6 were identified as the most frequently amplified genes by two groups respectively.…”
Section: Introductionmentioning
confidence: 99%